2008
DOI: 10.1227/01.neu.0000316009.19012.e3
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Was Not Associated With Less Vasospasm or Improved Outcome After Subarachnoid Hemorrhage

Abstract: The addition of statins to standard care was not associated with any reduction in the development of vasospasm or improvement in outcomes after aneurysmal subarachnoid hemorrhage. If there is a benefit to statin use, it may be smaller than suggested by previous studies. However, further randomized controlled trials are awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 34 publications
0
60
0
Order By: Relevance
“…However, other studies have shown that simvastatin does not exert a beneficial effect on patients with aSAH (8,9). Kramer et al (11) pointed out that if there is a benefit to statin use, it may be smaller than suggested by previous studies.…”
Section: Introductionmentioning
confidence: 92%
“…However, other studies have shown that simvastatin does not exert a beneficial effect on patients with aSAH (8,9). Kramer et al (11) pointed out that if there is a benefit to statin use, it may be smaller than suggested by previous studies.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, statins have been shown to enhance fibrinolysis and inhibit blood coagulation (Krysiak et al, 2003). However, a recent retrospective cohort study showed that after implementation of the routine use of statin treatment in SAH patients, the incidence of vasospasm, DCI, cerebral infarction, and poor outcome did not change (Kramer et al, 2008). Therefore, more randomized studies are needed to investigate the effect of acute statin treatment in patients with SAH, and whether statins exert cholesterol-dependent or independent effects in this group of patients.…”
Section: Studies Investigating Drugs To Prevent Delayed Cerebral Ischmentioning
confidence: 99%
“…It is strongly stimulated by interleukin-6 [1][2][3]6,7,[20][21][22][23] . Additionally, IL-1, which has been implicated in the pathogenesis of cerebral vasospasm, also provides a strong stimulus for CRP synthesis 1,[3][4][5] . Therefore, elevated CRP concentrations may well be associated with an increased possibility of developing cerebral vasospasm and subsequently a delayed ischemic neurological deficit (DIND) 1,3,[24][25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%